Legal Regulation of Electronic Voting Technologies in Kazakhstan - V. P. Kirilenko; N. S. Chimarov (Евразийская интеграция: экономика, право, политика, 2019)
The article dwells on the experience of the elections in Kazakhstan the technology of electronic voting. The authors analyze the evolution of the implementation of the new technology voting and the reasons of temporary rejection of her.